Removal of selected toxic metals by a modified adsorbent - Atalay E.; Gode F.; Sharma Y.C. (My University, 2025)
A modified method was used to increase the adsorption of heavy metals from aqueous solutions by using sawdust. Sawdust was collected from waste timber industry and modified with different tartaric acid concentrations (0.1 to 1.5 M) at 90°C for 90 min. The performance of the modified sawdust and unmodified sawdust have also been studied. The batch removal of the selected heavy metals, Cu(II), Zn(II), and Cd(II), from aqueous solutions under different experimental conditions was carried out in this study. The adsorption capacities of tartaric acid modified sawdust (TMSD) and nonmodified sawdust (NESD) were compared. The effect of initial metal concentration, temperature, pH, time, and adsorbent dosage on the removal of the metallic species have been reported. Two different of kinetic models viz. Lagergren-first-order and pseudosecond-order equations, were used to investigate the adsorption mechanism. The batch sorption kinetics and the applicability of the Langmuir, Freundlich, and Dubinin-Radushkevich adsorption isotherms for the present system have been tested at 25±2°C. NESD and TMSD were found to remove heavy metals from aqueous solutions efficiently. © 2010 ASCE.